Mathematical model of interaction between pollution and the environment: Mathematical model of interaction between pollution and the environment - Boborakhimova, M.I.; Asraqulova, D.S. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract. In this paper, a mathematical model of the interaction of pollution with the environment is formulated, taking into account the convective and diffusion processes of impurity propagation. A model is proposed in the form of a boundary value problem for a two-component nonlinear parabolic system. First, we prove the local existence and uniqueness of solutions. Next, we establish some a priori Schauder-type estimates and, on their basis, prove the global existence and uniqueness of solutions.